2019
DOI: 10.1177/0146167219829174
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood Is Associated With Greater Well-Being for Fathers Than Mothers

Abstract: The experiences of mothers and fathers are different in ways that could affect their well-being. Yet few studies have comprehensively examined gender differences in parents’ well-being. In the current research, we investigated such gender differences in a large representative sample (Study 1a; N = 13,007), in a community sample using validated well-being measures (Study 1b; N = 472), and in a large experience sampling study measuring happiness during caregiving activities and during interactions with children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 70 publications
8
63
2
7
Order By: Relevance
“…We emphasize that we are not saying that the attenuated interactions reported in these studies do not exist. Likewise, we emphasize that p-values in all studies with large sample sizes were close to or less than p = .01 (Sparks & Ledgerwood, 2019;Bahamondes et al, 2019;Nelson-Coffey et al, 2019). In two of the papers, authors also conducted internal metaanalyses across multiple studies, which yielded evidence that suggests effects are real (Wang & Ackerman, 2019;Hasan-Aslih et al, 2019).…”
Section: Tests Of Attenuated Interactions Are Common and Typically Unmentioning
confidence: 86%
“…We emphasize that we are not saying that the attenuated interactions reported in these studies do not exist. Likewise, we emphasize that p-values in all studies with large sample sizes were close to or less than p = .01 (Sparks & Ledgerwood, 2019;Bahamondes et al, 2019;Nelson-Coffey et al, 2019). In two of the papers, authors also conducted internal metaanalyses across multiple studies, which yielded evidence that suggests effects are real (Wang & Ackerman, 2019;Hasan-Aslih et al, 2019).…”
Section: Tests Of Attenuated Interactions Are Common and Typically Unmentioning
confidence: 86%
“…However, besides being rewarding, the transition can also be challenging, and put a strain on a couple's relationship (Kluwer, 2010). The positive effects of childbirth have been reported to be more pronounced for fathers than mothers (Balbo & Arpino, 2016;Nelson et al, 2013;Nelson-Coffey, Killingsworth, Layous, Cole, & Lyubomirsky, 2019). However, Polish panel data indicate a gender interaction that favors primiparous mothers' well-being (Baranowska & Matysiak, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy and parenthood have been associated with physical and psychological health through physiological and socioeconomic mechanisms in previous literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Previous epidemiological research also showed that parity and parenthood were related to major diseases, including cardiovascular [1,2], endocrine disease [3,4], and cancer [5].…”
Section: Introductionmentioning
confidence: 98%
“…There was also a growing body of literature focusing on the psychological impacts of pregnancy, parity, and parenthood [6][7][8][9][10][11][12][13][14]. Physiological research found that estrogen level was affected by women's reproductive history and subsequently influenced mental health outcomes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%